Metformin and risk of gingival/periodontal diseases in diabetes patients: A retrospective cohort study - Tseng, Chin-Hsiao (Frontiers in Endocrinology, 2022)
Aim: To compare the risk of gingival and periodontal diseases (GPD) between ever users and never users of metformin in patients with type 2 diabetes mellitus. Methods: The Taiwan’s National Health Insurance database was used to enroll 423,949 patients with new onset diabetes mellitus from 1999 to 2005. After excluding ineligible patients, 60,309 ever users and 5578 never users were followed up for the incidence of GPD from January 1, 2006 until December 31, 2011. Propensity score-weighted hazard ratios were estimated by Cox regression. Results: GPD was newly diagnosed in 18,528 ever users (incidence: 7746.51 per 100,000 person-years) and 2283 never users (incidence: 12158.59 per 100,000 person-years). The hazard ratio that compared ever users to never users was 0.627 (95% confidence interval: 0.600-0.655). When metformin use was categorized by tertiles of cumulative duration and cumulative dose, the risk significantly reduced in a dose-response pattern when the cumulative duration reached approximately 2 years or the cumulative dose reached 670 grams. Analyses on the tertiles of defined daily dose of metformin showed that the reduction of GPD risk could be seen in all three subgroups but the benefit would be greater when the daily dose increased. Conclusion: Long-term use of metformin is associated with a significantly reduced risk of GPD.